Ablation behavior and mechanisms of Cf/(Ti0.2Zr0.2Hf0.2Nb0.2Ta0.2)C–SiC high-entropy ceramic matrix composites. (15th August 2022) - Cai, Feiyan; Ni, Dewei; Bao, Weichao; Chen, Bowen; Lu, Jun; Zou, Xuegang; Qin, Yanyan; Dong, Shaoming
Abstract: For the first time, air plasma ablation behavior of Cf /(Ti0.2 Zr0.2 Hf0.2 Nb0.2 Ta0.2 )C–SiC high-entropy ceramic matrix composites was studied systematically under a heat flux of 5 MW/m 2, which provided a quasi-real hypersonic service environment at a temperature up to 2430 °C. The Cf /(Ti0.2 Zr0.2 Hf0.2 Nb0.2 Ta0.2 )C–SiC composites present excellent ablation-resistant performance with a linear recession rate of ∼2.89 μm/s and mass recession rate of ∼2.60 mg/s, which can be attributed to the dense and stable oxides layer formed on the sample surface. (Ti0.2 Zr0.2 Hf0.2 Nb0.2 Ta0.2 )C is oxidized to high-entropy oxide (TiZrHfNbTa)Ox at the ablation center and highly viscous SiO2 melt with uniformly dispersed (TiZrHfNbTa)Ox microspheres is formed. While at the edge of the ablation center, precipitation occurs during cooling and the oxides layer turns to a plate-like (Hf0.5 Zr0.5 O2 )' skeleton surrounded by (TiNbTaO7-y )' nanocrystals and continuous SiO2 melt. In contrast, oxidation of (Ti0.2 Zr0.2 Hf0.2 Nb0.2 Ta0.2 )C to produce (Hf0.5 Zr0.5 O2 )' and (TiNbTaO7-y )' is dominant at the ablation transition area and outer area with lower temperature. The multiphase oxides formed during ablation provide a stable and highly self-healing protective layer for the internal materials at ultra-high temperatures.